Understanding Jainism, by Lawrence A. Babb. Edinburgh: Dunedin, 2015. and Jainism: A Guide for the Perplexed, by Sherry Fohr. London & New York: Bloomsbury, 2015. (21st December 2017) - Appleton, Naomi
Abstract : Understanding Jainism, by Lawrence A. Babb. Edinburgh: Dunedin, 2015. 198 pp., £12.50 (pb). ISBN 978-1-780-46032-1 Jainism: A Guide for the Perplexed, by Sherry Fohr. London & New York: Bloomsbury, 2015. 176 pp., £54 (hb), £16.19 (pb and Ebook). ISBN 978-1-441-15116-2 (hb), 978-1-441-16594-7 (pb), 978-1-474-22755-1 (eBook)